The effects of PCR kits indicated during gene amplification of Panthera tigris amoyensis - Zhang, Xianfu; Zhao, Lin; Liu, Jianxun; Shi, Weibin; Hua, Keda; Wang, Yu; Yang, Xianyu (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
It is not rare that no product could be detected after polymerase chain reaction (PCR). During the cloning of some DNA segments of South China tiger (Panthera tigris amoyensis), it was found that different PCR kits gave different amplification results. To clarify this issue, a series of PCR was carried out by adopting different PCR kits, PCR tubes and Thermal Cyclers from different manufactures. Among 4 DNA segments (A-D), D was amplified well regardless of PCR kits, A was amplified well only with real-time quantitative fluorescent PCR kit, meanwhile the amplification of B and C showed different levels depending on the PCR kits. All these results indicated the importance of PCR kits, while neither Thermal Cyclers nor PCR tubes affect the PCR products.